1997
DOI: 10.1074/jbc.272.20.13397
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated Protein (MAP) Kinase Regulates Production of Tumor Necrosis Factor-α and Release of Arachidonic Acid in Mast Cells

Abstract: Aggregation of the high affinity IgE receptor (Fc⑀RI) in a mast cell line resulted in activation of the p42 and the stress-activated p38 mitogen-activated protein (MAP) kinases. Selective inhibition of these respective kinases with PD 098059 and SB 203580 indicated that p42 MAP kinase, but not p38 MAP kinase, contributed to the production of the cytokine, tumor necrosis factor-␣, and the release of arachidonic acid in these cells. Neither kinase, however, was essential for Fc⑀RI-mediated degranulation or const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
155
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(173 citation statements)
references
References 35 publications
17
155
1
Order By: Relevance
“…Previous studies have demonstrated that activation of PKC and elevation of intracellular Ca 2ϩ are sufficient and necessary for the release of these inflammatory mediators from granules (85)(86)(87). By contrast, studies have shown that the MAPKs are not required for the release of these inflammatory mediators, but are involved in the production of arachidonic acid and cytokines (27,33,88). Here we demonstrate that PLC␥2 deficiency partially impaired Ca 2ϩ signals following engagement of the Fc⑀R in mast cells, resulting in a reduced Fc⑀R-mediated release of serotonin, histamine, and arachidonic acid, but had no effect on cytokine transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that activation of PKC and elevation of intracellular Ca 2ϩ are sufficient and necessary for the release of these inflammatory mediators from granules (85)(86)(87). By contrast, studies have shown that the MAPKs are not required for the release of these inflammatory mediators, but are involved in the production of arachidonic acid and cytokines (27,33,88). Here we demonstrate that PLC␥2 deficiency partially impaired Ca 2ϩ signals following engagement of the Fc⑀R in mast cells, resulting in a reduced Fc⑀R-mediated release of serotonin, histamine, and arachidonic acid, but had no effect on cytokine transcription.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the activation of ERKs follows stimulation of basophils with FMLP or anti-IgE Ab and appears to be responsible for free AA/LTC 4 generation by phosphorylating cPLA 2 , because PD98059 inhibits ERK and cPLA 2 phosphorylation and selectively inhibits LTC 4 release, but not histamine release or IL-4 production, in human basophils (15). A variety of studies in other cell models also suggest that ERKs are responsible for phosphorylating cPLA 2 (31,39,40). The current study shows that treatment by IL-3 or stimulation by C5a results in ERK phosphorylation that is inhibitable by PD98059 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PD98059 is thought to be a specific inhibitor of MEK1/2, the immediately antecedent kinases to the ERKs (15,30,31). This compound is often used to determine the involvement of MEK/ERK activation.…”
Section: Phosphorylation Of Erks (Erk1 and Erk2) And Of Cpla 2 Inducementioning
confidence: 99%
“…In RBL cells, secretion of newly synthesized LTC 4 and TNF-␣, but not histamine release, requires activation of the MAPK pathway, specifically MEK and ERK-2 (29). We compared Fc⑀RI-stimulated phosphorylation of MEK and ERK-2 between our two Lyn unique domain transfectants and a control transfectant.…”
Section: Kinetics Of Mapk Activation Stimulated By Fc⑀ri Aggregation mentioning
confidence: 99%